Effect of Cooking Methods on Quality Characteristics of Nuggets and Patties from Sheep, Goat and Rabbit Meat - Sen, A.R.; Karim, S.A. (Journal of Meat Science, 2011)
The effect of cooking methods (moist vs dry heat) on physicochemical and sensory attributes of sheep, goat and rabbit meat products was studied. The cooking yield % was significantly (P
Keywords: Cooking method; mutton product; rabbit meat product; physico-chemical quality